Bonds of Hercules - Mas, Jasmine (Mas, Jasmine. Villains of lore, 2025)
"I'm Hercules, but my powers are not what they seem. I'm trapped in a marriage with my two enemies and I've accidentally joined a cult. To make matters worse, Augustus and Kharon are trying to seduce me. It doesn't help that my mentors, Achilles and Patro, are acting really strange. Now, a dangerous prisoner has escaped from the Underworld, and things are spiraling out of control. Men are fighting over me. Mysteries are unfolding left and right. And I've had enough. Everybody better beware because I'm fighting in the Gladiator Competition and seizing my power. Things are about to get very messy. For Sparta." --